How we established a new undergraduate firm on a Medical Admissions Unit. (November 2014) - Nazir, Tahir; Wallis, Simon; Higham, Jackie; Newton, Kate; Pugh, Mark; Woywodt, Alexander
Abstract Medical Admission Units (MAUs) were introduced in the UK in the 1980s primarily driven by a governance and service improvement agenda. In the UK this has led to the development of Acute Medicine as a specialty in its own right, together with a strong role of this specialty in postgraduate teaching. In contrast, the role of MAUs, if any, in undergraduate medical education is currently unclear. Prompted by an expansion of our undergraduate student numbers, our aim was to establish a Year 3 undergraduate firm on a 33-bedded MAU in a large academic teaching hospital in the National Health Service (NHS). Despite initial scepticism from clinicians, managers, and educators, the new firm placement on MAU became an instant success and continues to attract excellent feedback from our Year 3 undergraduate students. Students enjoy the bedside teaching with a high percentage of consultant-delivered teaching and also liked the involvement of Foundation Doctors. Here, we report our experience on how to make such a firm work, based on student feedback and the tutors' experience. We provide an overview and a step-by-step guide of how to construct a successful new undergraduate firm on a busy MAU. We also discuss opportunities and challenges and discuss the relevant literature. We conclude that undergraduate teaching is feasible and rewarding in an extremely busy MAU setting. We note that identifying enthusiastic educators within the MAU team, utilisation of peripheral learning opportunities, structured timetables and induction, and a robust framework for quality assurance are all crucial to success.